(untitled) - Jones, Leo (London, 2002)
Many people,learning English as a second language attend language centers and this or that way, receive certificates; nonetheless, at the end of the day, they still have problems with conversation. Let's Talk series is excellent for people who want to improve their conversation skills.The series consist of three books and cassettes and audio CDs are very helpful and also enables self-learning. This set is filling an important gap in Teaching and Learning English as far as conversation skills are concerned.
Keywords: English language; Textbooks for foreign speakers